The correlation between learning styles and self–directed learning of fifth graders - Truong Phan Nguyen Dong; Tuong Nguyen Van (Institute of Advanced Engineering and Science, 2022)
Vietnam education has been directed into a learner-centered approach and fostering competencies for students, especially self-directed learning. Thus, understanding how students’ learning styles impact self-directed learning are crucial for the new direction of Vietnam education. This research employed the survey method by questionnaire and presents the results of practical research on the correlation between styles of learning and self–directed learning of fifth-grade students at elementary schools in District 10, Ho Chi Minh City, Vietnam. The sample was 364 fifth graders voluntarily participating in the survey with the consent of parents. The results indicated that learning styles are strongly correlated with self–directed learning competency of fifth graders. The data revealed that students at District 10 not only attained high self-directed learning levels but also their learning styles attributing impactfully on their self-directed learning competency.